Pengembangan E-Modul Berbasis Socio-Scientific Issues (SSI) pada Materi Kesetimbangan Benda Tegar untuk Meningkatkan Literasi Sains - Secho Nur Faizah; Sugianto (Unnes Physics Education Journal, 2025)
Science literacy is one of the skills of learners who are still low. The development of teaching materials focusing on real-world environmental issues by integrating technology through the Socio-Scientific Issues (SSI) approach is expected to improve the science literacy skills of 21st century learners. This study aims to determine the feasibility, effectiveness, and practicality of e-modules in improving the ability of science literacy of students. This research is included in Research & Development (R&D) research with the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluate). At the implementation stage, the experimental design used was a pre-experimental design with a one group pretest-posttest design approach. The subjects in the study involved 35 students XI-5 SMAN 3 Tegal determined through purposive sampling technique. The data collection instruments used were expert validation sheets, science literacy tests, and student response questionnaires. The results showed that the developed e-module was valid and feasible to use in learning with a validity score of 94% on the material aspect and 95% on the media aspect, both of which were included in the “very feasible” category. The results of the trial use of e-modules obtained an average N-gain score of 0.50 with a “moderate” improvement category. The e-module obtained a percentage of practicality from students' responses of 83% with the category “very practical” so that it is easy to use in learning. The developed SSI-based e-module meets the criteria of valid, effective, and practical to improve students' science literacy.